ANALISIS PENGARUH HARGA DAN KUALITAS PELAYANAN YANG BERPENGARUH TERHADAP KEPUASAN PELANGGAN DAN BERTUJUAN UNTUK MENINGKATKAN LOYALITAS PELANGGAN CITILINK DI SEMARANG - Naufal, Muhammad Arif; Yoestini, Yoestini (Diponegoro Journal of Management, 2019)
Business competition in the airline industry is quite strict, and cannot be avoided. Ittakes a lot of innovations and knowledges of what needs are needed by the community sothat people will be loyal to the product. The purpose of this study is to find out the effect ofprice and service quality that affect customer satisfaction which may also have an impacton customer loyaltyThe purpose of this study is to find out the effect of price and service quality thataffect customer satisfaction which may also have an impact on customer loyalty. Thepopulation in this study was airline consumers in the city of Semarang. The number ofsample used was 126 people selected using nonprobability sampling and purposivesampling through questionnaires. The results showed that price affects customersatisfaction, service quality affects customer satisfaction, and customer satisfaction affectscustomer loyalty. In this study service quality is the most influential variable on customersatisfaction. Customer satisfaction is also found to have a mediating function in theinfluence relationship between price and service quality to customer loyalty.